HARTA WARIS PADA ANAK ANGKAT MENURUT KOMPILASI HUKUM ISLAM DI PENGADILAN AGAMA SAMARINDA - Abdul Rokhim (Universitas 17 Agustus 1945 Samarinda, 2020)
In general, adoption according to law is the transfer of a child to adoptive parents from the biological parents in its entirety and is carried out according to legal local customs. So, the biological parents have let go of the child, and the responsibility shifts to the parents who adopted him. Although the Qur'an does not give adopted children the right to inherit from their adoptive parents, this is regulated in the Compilation of Islamic Law which is a human product from various schools of thought and made as a source of law in our country by providing provisions. that adopted children are entitled to receive a share of the inheritance.The legal position of the adopted child will result in that in general the child will have an inheritance relationship with the adoptive parents and inherit from the original parent will be removed based on Article 209 Paragraph 2 Compilation of Islamic Law (KHI), adopted children who do not receive a will will be given mandatory will. The position of adopted children according to Islamic inheritance law is not getting their inheritance rights from their adoptive parents, but still as legitimate children based on a court decision by not deciding the lineage / blood with their biological parents, because the principle of adoption according to the Islamic Law Compilation is a manifestation of faith that carrying a humanitarian mission that is manifested in the form of maintenance in its growth and development by fulfilling all its needs.Regarding the distribution of inheritance in the Compilation of Islamic Law Article 209 paragraph (2) for adopted children who do not receive a will but are given what is called a will, obligatory maximum of 1/3 (one third) of the inheritance of their adoptive parents, as stated in Article 195 paragraph (2) will allow a maximum will of only 1/3 of the inheritance unless all the heirs agree.